Characterization of nanolayered coatings for advanced applications - Too, Andre Yun Hui (2016)
Tool wear takes up a major portion of the costs in the machining industry. Nanolayered superlattice structure has great potential in the area of tool coatings due to their considerable strengthening mechanisms. The improved properties of the structure allows for cost reduction in tool replacements. This thesis illustrates the study of the microstructure through using different characterization techniques and providing information on the source of properties. Using the physical deposition method of cathodic arc evaporation, TiN/TiAlN coatings were deposited on cemented carbide substrates. The coatings were characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray Diffraction (XRD) and nano indentation. Microdroplets were found on the surface of the coating from SEM observations. The TEM data showed that period thickness was dependent on the deposition rotation speed. Both TEM and XRD methods identified TiN phase and {111} columnar grain growth texture perpendicular to the substrate without any noticeable defects. The appearance of spotty ring and broad peaks indicated that the coatings were polycrystalline. Higher rotation speed of 4rpm and above results in the stabilization of epitaxial superlattice structure. The superlattice structure is identified by the satellite peaks in the diffractogram. Peak hardness was found to be at 5rpm with competing strengthening factors of strain hardening and Hall-Petch relation.